Konseptualisasi dan Dinamika Ijtihad: Telaah atas Metodologi, Produk Hukum, dan Implikasinya terhadap Modernisasi Hukum Islam - R, Rahmatullah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This article examines ijtihad as a method of thinking in Islamic law, by highlighting the definition, requirements of mujtahid, methodological stages, as well as the variety of classical to contemporary methods of ijtihad. Ijtihad is an important instrument in maintaining the relevance of Islamic law to the dynamics of the times and developments of society. In the classical tradition, ijtihad is practiced individually by scholars who meet the strict requirements of science and morality. As for the modern era, ijtihad developed in a collective form through official institutions, allowing for a more contextualized multidisciplinary approach. Methods such as qiyas, maslahah mursalah, istishab, and istishab become the main tools in the process of ijtihad, which should always be directed at the attainment of maqashid al-shari‘ah. Thus, ijtihad is not only a reflection of intellectual creativity, but also an adaptive mechanism in ensuring that Islamic law remains solutive and applicative in a variety of situations.